S1: Active volcanoes in Marie Byrd Land - N.W. Dunbar (9720275); N.A. Iverson (9720278); J.L. Smellie (9004769); W.C. McIntosh (9003089); M.J. Zimmerer (9003086); P.R. Kyle (9610841) (2021)
Detailed locations, descriptions and geochemistry of Mount Waesche englacial tephra layers, along with selected other samples, and description of Mount Waesche field campaigns.